Challenges in enabling aging-in-place initiatives in aging and shrinking Japanese cities: a case of the Gifu suburbs - Tomoko Kubo; Nobuhiko Komaki; Kensaku Tanaka (Boletín de la Asociación de Geógrafos Españoles)
This study first reviewed previous literature on 1) the residential environments and everyday lives of older adults to examine universal factors enabling aging-in-place initiatives, and 2) the generation and outcomes of aging and shrinking suburbs in the Japanese context, via comparisons with case studies in Western cities. A case study was then conducted in the suburbs of Gifu to provide a clear impression of older adults’ daily lives and their perceived barriers in aging and shrinking suburbs in Japan. Finally, we discussed challenges involved in enabling aging-in-place initiatives whose major goal is to provide residential environments in which older adults can maintain continuous residency in their attached homes and neighborhoods in Japanese cities. The case study revealed that many older adults wished to continue living in their homes and neighborhoods. Diversification of accessible support in families and modification of interrelationships among family, housing, and welfare can contribute to adjustments in later life. Systems to support mobility after ceasing driving should be examined in more detail, because older adults were not satisfied with bus service quality, resulting in individuals postponing the decision to cease driving. To enable aging-in-place initiatives in Japan, cooperation among different ministries in national government and divisions at the municipal level is necessary.